Designing for the digital age : how to create human-centered products and services - Goodwin, Kim , 1971- (Wiley Publishing, 2009)
Designing successful products and services in the digital age requires a multi-disciplinary team with expertise in interaction design, visual design, and industrial design. This title covers topics including assembling a design team, planning and conducting user research, and analyzing your data and turning it into personas